2D perovskite or organic material matter? Targeted growth for efficient perovskite solar cells with efficiency exceeding 24%. (April 2022) - Wang, Pengyang; Chen, Bingbing; Li, Renjie; Wang, Sanlong; Li, Yucheng; Du, Xiaona; Zhao, Ying; Zhang, Xiaodan
Abstract: Defects at the surface and grain boundaries at the interface between perovskite and electron transport layer (ETL) induce severe non-radiative recombination, detrimental to device's performance and stability. Organic materials are often used for surface passivation, but most works ascribed the great passivation ability to the formed two-dimensional (2D) perovskite. Here, we demonstrated that the organic halide salt hexaneammonium iodide (HAI) targets growth at grain boundaries and plays a critical role in suppressing the charge recombination instead of forming quasi-2D or 2D perovskite to passivate the surface defects. Moreover, the HAI invested the perovskite films with superhydrophobicity, enhancing the moisture resistance and preventing the diffusion of Li + into perovskite films. As a result, boosting the efficiency of PSCs from 22.38% to 24.07% (certified efficiency of 23.59%) with a voltage deficit of 0.35 V. The surface treatment also enhances the operational stability of perovskite solar cells (PSCs), unencapsulated devices maintain 81.4% of their initial efficiency for 200 h under continuous light irradiation in the N2 atmosphere. Graphical Abstract: ga1 Highlights: The spin-coated organic salt targeted growth at grain boundaries. The organic salt plays a critical role instead of forming quasi-2D or 2D perovskite to passivate the surface defects. An efficient PSC with 24.07% (certified efficiency of 23.59%) is fabricated. Enhanced moisture resistance and preventing the diffusion of Li + into perovskite films.